Called and Chosen as Servants of God: A Study of the Theology of Pastoral Ordination in the Midst of Church Ministry - Siahaan, Tunas Irwandi; Sitanggang, Pintor Marihot (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2025)
Pastoral ordination or ordination is a part of the church system that has deep theological meaning. The process of giving (ordination) is not only a church rite or ceremony, but reflects God's unique call for someone to serve as a servant of God in the capacity of a pastor. In Christian theology, this calling and ordination is considered an important part of the true and holy structure of the church, where a pastor is sent to nurture, teach, and guide the congregation towards maturity in the faith. This article explains how ministers of ordained pastors believe that God's calling and election of them is their calling and election as God's servants who serve in the church. To achieve the aim of this article, this article will begin by exploring biblical studies regarding the election and calling of God's servants. This is then continued with a theological discussion about ordination theology and how to contextualize God's servants in pastors in the midst of church services.